PENINGKATAN HASIL BELAJAR MENGGIRING BOLA PERMAINAN SEPAKBOLA MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISIONS - Muhammad Hasbillah; Ikadarny Ikadarny; Suparman Suparman; Suastika Nurafiati; Ariana Asri; Achmad Karim; Herman Herman (Riyadhoh : Jurnal Pendidikan Olahraga, 2022)
This research is a classroom action research conducted in four meetings in cycle I and II, and is designed through four stages: planning, implementing, and reflecting. The data source for this research was 18 students in class V at SD Negeri 375 Tancung, Wajo Regency. Collecting data on the ability to dribble using assesment sheets for starting technique, body position, foot contact with the ball, and final attitude. The results of quantitative analysis of the learning outcomes of dribbling in football games showed that the number of students who completed the first cycle was 11 people with a percentage of 64,70% and the number of students who completed the second cycle were 17 people with a percentage of 100%. Based on the results of this study, it can be concluded that learning physical education through cooperative learning models of the Student Team Achievement Divisions type can improve the learning outcomes of dribbling in football games for fifth grade students at SD Negeri 375 Tancung, Wajo Regency.